In-situ dual-phase vanadium-based hydrogen storage material as well as preparation method and application thereof

In-situ dual-phase vanadium-based hydrogen storage materials are prepared through vacuum heat treatment and ball milling reaction, and titanium tetrachloride is used as a catalytic grinding aid. This solves the problems of high energy consumption and single modification strategy in the preparation of vanadium-based hydrogen storage materials, and achieves low-cost and efficient performance improvement of vanadium-based hydrogen storage materials, which is suitable for a variety of hydrogen storage scenarios.

CN120646760APending Publication Date: 2025-09-16XIAN TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510829782.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

The preparation of existing vanadium-based hydrogen storage materials requires high energy consumption and cost, and the modification strategy is single. The activation performance and hydrogen absorption kinetics are not ideal, making it difficult to adapt to large-scale industrial production.

Method used

The in-situ dual-phase vanadium-based hydrogen storage material was prepared by vacuum heat treatment and hydrogenation crushing of vanadium blocks, followed by ball milling reaction with titanium tetrachloride and further heat treatment. Titanium tetrachloride was used as a catalytic grinding aid, and the process flow was simplified by mechanical alloying.

Benefits of technology

It significantly improves the activation and kinetic properties of vanadium-based hydrogen storage materials, reduces preparation costs, and is suitable for large-scale industrial production. It is also used in fuel cell hydrogen supply, hydrogen compression systems, hydrogen storage tanks at hydrogen refueling stations, and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120646760A_ABST
    Figure CN120646760A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of hydrogen storage materials, in particular to an in-situ dual-phase vanadium-based hydrogen storage material as well as preparation and application thereof. The preparation method comprises the steps that after vanadium blocks are subjected to vacuum heat treatment, hydrogen pressure is added at the room temperature for hydrogenation crushing, and vanadium particles are obtained; carrying out ball milling on the vanadium particles and the titanium tetrachloride catalytic grinding-aid phase; and carrying out one-step heat treatment on the ball-milled product in a vacuum environment to prepare the in-situ dual-phase vanadium-based hydrogen storage material. On the basis of ensuring the hydrogen storage capacity of the material, the activation performance and the dynamic performance of the vanadium-based hydrogen storage material are improved, the reversible hydrogen storage capacity at 30 DEG C is 1.83 wt%, the hydrogen desorption platform pressure is 2.61 bar, and the reversible hydrogen storage capacity after 5 times of hydrogen absorption and desorption cycles at 30 DEG C is 1.87 wt%; a new strategy is provided for improving the hydrogen absorption and desorption performance of the vanadium-based hydrogen storage material; the preparation method disclosed by the invention is simple in preparation process and operation, short in production period and low in energy consumption; the product is wide in application range, is suitable for large-scale industrial production, and can be comprehensively applied to solid hydrogen storage aspects such as fuel cell hydrogen supply, a hydrogen compression system, a hydrogen refueling station hydrogen storage tank and a distributed energy hydrogen storage tank.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state hydrogen storage, and in particular to an in-situ dual-phase vanadium-based hydrogen storage material, a preparation method and applications thereof. Background Art

[0002] Energy is fundamental to human survival and social development. Against the backdrop of global economic integration, energy demand continues to grow. However, fossil fuel reserves are limited, and the widespread development and utilization of fossil fuels like coal and oil has led to serious environmental pollution. Hydrogen, as an energy carrier with abundant reserves, high mass energy storage density, and zero emissions, has been recognized as the most promising form of clean energy. The hydrogen energy industry chain encompasses hydrogen production, storage, transportation, and applications. On the hydrogen production side, various methods exist for producing hydrogen, including coke oven gas, natural gas reforming, and electricity generated from resources like sunlight, hydropower, and wind power. On the hydrogen application side, the number of hydrogen refueling stations in China has been growing rapidly since 2020. According to the Hydrogen Energy Alliance, by June 2024, my country had built 507 hydrogen refueling stations, the largest number globally and leading the world in growth. Relatively speaking, as an intermediate link in the hydrogen energy industry standard system, domestic companies are still in the stage of technological breakthroughs in the field of hydrogen storage materials, and there is a large gap between storage technology and foreign countries. Therefore, seeking safe and efficient hydrogen storage technology has become the key to the development of the hydrogen energy industry.

[0003] Vanadium-based alloys are solid solution hydrogen storage alloys with a body-centered cubic (BCC) structure. These alloys exhibit hydrogen adsorption and release capabilities at room temperature, with theoretical hydrogen storage capacities as high as 3.8 wt%, approximately three times that of LaNi5H6 alloys. However, the high thermodynamic stability of their low-temperature phases reduces their effective hydrogen storage capacity, limiting further development of vanadium-based alloys. Despite this, the reversible storage capacity of vanadium-based solid solutions remains higher than that of existing AB5- and AB2-type alloys. To improve the hydrogen storage performance of vanadium-based solid solution hydrogen storage materials, the main approach currently employed is to alloy them with vanadium by introducing transition metals or rare earth metals (such as Ti, Cr, Mn, Ni, and Zr) as alloying elements [Huang Zhengguang et al., Energy. 2025, 316:134574], [Yukawa H et al., Journal of Alloys and Compounds. 2002, 330–332:105]. This can significantly influence activation characteristics, hydrogen storage capacity, and plateau pressure. Different elements have different effects on the hydrogen absorption and desorption properties of vanadium-based alloys due to differences in their atomic radius and electronic structure [Balcerzak M, International Journal of Hydrogen Energy, 2020, 45(31): 15521–15529]. Both Ti and V exhibit excellent hydrogen storage properties, so Ti, as one of the alloying elements, has been widely studied in the early days. Ti can form a solid solution with V in a wide range. V-Ti binary alloys are usually used as the basis for the development of multi-component V-based alloys. Matsuda conducted an experimental study on the hydrogen storage performance of V-Ti alloys with different proportions, and explored the changes in the microstructure of the alloy during hydrogen adsorption. The results show that V x Ti 1-x In the alloys (x = 0.2, 0.4, 0.5 and 0.6), V 0.8 Ti 0.2 The alloy's PCT curve for hydrogen absorption and desorption exhibits the flattest characteristics, with a maximum hydrogen storage content of 1.6 wt%. Studies have also revealed that the introduction of Ti reduces the dehydrogenation pressure and increases the standard reaction enthalpy [Junko Matsudag et al., Journal of Alloys and Compounds, 2013, 581, 369-372].

[0004] However, most V-based alloys, including VTi-based alloys, are currently prepared using a smelting method. Publication No. CN114381644 B discloses a "Vanadium-Titanium-Based Hydrogen Storage Alloy Powder and Preparation Method Thereof," which includes the following steps: A. Using a vanadium-titanium-based hydrogen storage alloy ingot obtained by smelting and casting as raw material, the vanadium-titanium-based hydrogen storage alloy is placed in a heat treatment furnace and heated in a mixed atmosphere of hydrogen and inert gas, followed by a low-temperature hydrogen absorption treatment; B. The hydrogen storage alloy is coarsely crushed to a designed particle size to obtain a semi-finished product; and C. The semi-finished product is converted into a vanadium-titanium-based hydrogen storage alloy powder under protective atmosphere. Problems with the existing technology include: 1. The modification strategy for vanadium-based hydrogen storage materials is monotonous, employing multiple elements and requiring complex inter-element design; 2. Due to the smelting method, the process is energy-intensive and costly, making it unsuitable for large-scale industrial production; and 3. The activation performance and hydrogen absorption kinetics are suboptimal and need to be further improved. Summary of the Invention

[0005] The present invention aims to provide an in-situ dual-phase vanadium-based hydrogen storage material, a preparation method and its application, so as to overcome the problems of high energy consumption, high cost and single modification strategy in the preparation of vanadium-based hydrogen storage materials in the prior art.

[0006] To achieve the above objectives, the present invention provides a specific technical solution as follows: a method for preparing an in-situ dual-phase vanadium-based hydrogen storage material, comprising: subjecting a vanadium block to vacuum heat treatment, adding hydrogen pressure at room temperature for hydrogenation and crushing to obtain vanadium particles; mixing the vanadium particles with titanium tetrachloride and subjecting them to a ball milling reaction; and further subjecting the mixture to a further heat treatment step to obtain the dual-phase vanadium-based hydrogen storage material.

[0007] Furthermore, the vacuum heat treatment temperature is 500-600°C.

[0008] Furthermore, the hydrogen pressure of the hydrogenation crushing is 50 to 100 bar.

[0009] Furthermore, the vacuum heat treatment and hydrogenation treatment are performed 3-5 times.

[0010] Furthermore, the ball milling reaction is carried out at room temperature in an inert atmosphere or a vacuum environment.

[0011] Furthermore, the mass ratio of the vanadium particles to titanium tetrachloride is 20 to 100:1.

[0012] Furthermore, the ball milling method is planetary ball milling, using stainless steel beads, a ball-to-material ratio of 30 to 100:1, a ball milling speed of 300 to 400 rpm, and a ball milling time of 3 to 6 hours.

[0013] Furthermore, the above-mentioned heat treatment step is carried out in a vacuum environment at a temperature of 500-600° C. for 2-3 hours.

[0014] Furthermore, the above preparation method produces an in-situ dual-phase vanadium-based hydrogen storage material.

[0015] Furthermore, the above-mentioned in-situ dual-phase vanadium-based hydrogen storage material is used in the field of solid-state hydrogen storage.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] 1. The present invention addresses the current problems of poor activation performance and poor hydrogen absorption kinetics of existing V solid solution hydrogen storage alloys. It studies the alloy's microstructure formation and its hydrogen storage performance, and analyzes the change mechanism of hydrogen storage performance from a kinetic perspective. This provides a simple, low-cost method for improving the performance of V-based hydrogen storage materials. Titanium tetrachloride is creatively introduced as a catalytic grinding aid into vanadium-based hydrogen storage materials, providing a simple and efficient way to obtain V-based two-phase hydrogen storage alloys in situ through mechanical alloying. Specifically, from the perspective of raw materials, vanadium blocks are selected for hydrogenation and crushing because commercially available pure vanadium powder is easily oxidized. Titanium tetrachloride is selected as a grinding aid because it is low-cost, is the main raw material for preparing sponge titanium, and can also be used as a catalyst for hydrogen storage materials. In summary, this application uses titanium tetrachloride as a grinding aid and ball mills with hydrogenated and crushed vanadium particles to in situ prepare a V-based two-phase hydrogen storage alloy, whose activation performance is significantly improved. The reversible hydrogen storage capacity at 30°C is 1.83wt%, the hydrogen desorption platform pressure is 2.61bar, and the reversible hydrogen storage capacity after 5 cycles of hydrogen absorption and desorption at 30°C is 1.87wt%.

[0018] 2. The preparation process and operation method of the present invention are simple, and the in-situ dual-phase vanadium-based hydrogen storage material is prepared by a simple process of mechanical alloying and heat treatment. Specifically, the dual-phase VTi-based hydrogen storage material is prepared in situ by means of ball milling combined with heat treatment. The raw material is cheap TiCl4, and the ball milling speed is only 300 rpm, and the heat treatment temperature is only 500°C, which is much lower than the temperature and energy consumption required for smelting. At the same time, the full preparation cycle time of the material of the present invention is only 6 hours, and the product composition is uniform, the activation performance is excellent, the hydrogen absorption and desorption kinetics are fast, and the cycle stability is high. In addition, during the preparation process, although the hydrogen storage inert phase TiCl4 is introduced, the hydrogen storage capacity of the V-based material is not significantly sacrificed. Therefore, the method provided by the present invention is a low-cost, short-cycle preparation method that can improve the activation performance, kinetic performance and cycle stability of the V-based hydrogen storage material without sacrificing the hydrogen storage capacity of the material, and is suitable for large-scale industrial production.

[0019] 3. This invention provides a new strategy and theoretical support for improving the hydrogen storage performance of vanadium-based solid solution hydrogen storage alloys, effectively enhancing the activation and kinetic properties of vanadium-based hydrogen storage materials. The products of this invention have a wide range of applications, including fuel cell hydrogen supply, hydrogen compression systems, hydrogen storage tanks for hydrogen refueling stations, and distributed energy hydrogen storage tanks for solid-state hydrogen storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an X-ray diffraction pattern of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 1 of the present invention;

[0021] Figure 2 The SEM morphology of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 1 of the present invention and the EDS spectrum of the corresponding area;

[0022] Figure 3 (a), (b) and (c) are respectively the V 2p XPS spectrum, Ti 2p XPS spectrum and Cl 2p XPS spectrum of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 1;

[0023] Figure 4 This is a graph showing the isothermal hydrogen absorption curve of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 1 of the present invention when first activated at 30°C;

[0024] Figure 5 (a) and (b) are respectively the isothermal hydrogen absorption kinetics curves and Arrhenius curves of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 1 of the present invention at 30° C., 50° C., 80° C., and 100° C.;

[0025] Figure 6 The PCT curves of hydrogen release of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 1 of the present invention at 30° C., 50° C., and 80° C. are shown;

[0026] Figure 7 The PCT curves of hydrogen release at 30°C of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 1 of the present invention before and after 5 cycles;

[0027] Figure 8 This is an X-ray diffraction pattern of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 2 of the present invention;

[0028] Figure 9 (a), (b) and (c) are respectively the V 2p XPS spectrum, Ti 2p XPS spectrum and Cl 2p XPS spectrum of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 2;

[0029] Figure 10 This is a graph showing the isothermal hydrogen absorption kinetics of the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 2 of the present invention at 30° C. when first activated;

[0030] Figure 11 This is a PCT curve of hydrogen release at 50° C. for the in-situ dual-phase vanadium-based hydrogen storage material prepared in Example 2 of the present invention;

[0031] Figure 12This is a graph showing the isothermal hydrogen absorption kinetics at 30° C. of the V particles prepared in Comparative Example 1 of the present invention when first activated;

[0032] Figure 13 (a) and (b) are the isothermal hydrogen absorption kinetics curves of the V particles prepared in this comparative example at 30°C, 50°C, 80°C, and 100°C, and the corresponding Arrhenius curves. DETAILED DESCRIPTION

[0033] The present invention will be described in detail below with reference to embodiments and accompanying drawings.

[0034] Example 1, a method for preparing an in-situ dual-phase vanadium-based hydrogen storage material, comprising the following steps:

[0035] Step 1: Heat the vanadium block to 500°C under vacuum conditions for 1 hour, cool it to room temperature, and then fill it with 60 bar of hydrogen pressure for 6 hours. Repeat the above vacuum heat treatment and hydrogenation crushing operations 4 times to obtain crushed vanadium particles.

[0036] Step 2: In an argon atmosphere glove box, vanadium particles (1 g) and titanium tetrachloride were mixed in a mass ratio of 10:1 and placed in a sealed stainless steel ball mill jar. Stainless steel grinding balls were used with a ball-to-material ratio of 50:1 and a ball milling speed of 300 rpm. The ball milled product was obtained after 3 h of ball milling.

[0037] Step 3: Heat the ball-milled product to 500° C. under vacuum, keep the temperature for 2 hours, and then cool it down to obtain an in-situ dual-phase vanadium-based hydrogen storage material.

[0038] Figure 1 This is the X-ray diffraction (XRD) pattern of the in-situ dual-phase vanadium-based hydrogen storage material. Only a single diffraction peak of V is observed in the material, and no other components exist or other components exist in amorphous form.

[0039] Figure 2 (a) and (b) show the SEM morphologies of this in-situ dual-phase vanadium-based hydrogen storage material at different magnifications, and (c) shows the EDS spectrum of the selected area in (a). The alloy exhibits a flaky structure. The spectrum results reveal a relatively uniform distribution of V within each sample, as well as uniform distribution of Ti and Cl within each particle.

[0040] Figure 3 (a), (b) and (c) are the V 2p XPS spectra, Ti 2p XPS spectra and Cl 2p XPS spectra of the in-situ dual-phase vanadium-based hydrogen storage material, respectively. It can be seen that the V in the material is mainly 0-valent V, accompanied by a small amount of V 4+ , Ti then exists at the same time 4+ and Ti 0, and the XPS signal of Cl can still be observed. This indicates the presence of Ti(V)Cl4 phase and VTi solid solution phase in the material. Specifically, TiCl4 acts as a catalytic grinding-aid phase and is ball-milled with crushed V particles, followed by further heat treatment to obtain a VTi-based dual-phase hydrogen storage alloy doped with Ti(V)Cl4 in situ.

[0041] Figure 4 This is the isothermal hydrogen absorption curve of the in-situ dual-phase vanadium-based hydrogen storage material when it is first activated at 30°C. It can be seen that the prepared vanadium-based hydrogen storage material adsorbs more than 3.5wt% H2 within 770s, reaches the maximum value at around 3000s, and the maximum hydrogen absorption capacity can reach 3.84wt%.

[0042] Figure 5 (a) is the isothermal hydrogen absorption kinetics curve of the in-situ dual-phase vanadium-based hydrogen storage material at 30°C, 50°C, 80°C, and 100°C. (b) is the Arrhenius curve plotted based on the isothermal hydrogen absorption kinetics curves at different temperatures. The calculated hydrogen absorption activation energy is 5.57 kJ·mol -1 . Shows excellent hydrogen absorption kinetics.

[0043] Figure 6 The PCT curves of hydrogen desorption of the in-situ dual-phase vanadium-based hydrogen storage material at 30°C, 50°C and 80°C are shown. The platform pressures at 30°C, 50°C and 80°C are 2.61, 8.88 and 27.1 bar, respectively, and the corresponding effective hydrogen desorption capacities are 1.83wt%, 1.78wt% and 1.73wt%, respectively.

[0044] Figure 7 The PCT curve of hydrogen release at 30°C of the in-situ dual-phase vanadium-based hydrogen storage material before and after 5 cycles shows that the effective hydrogen storage capacity at 30°C after the cycle is 1.87wt%, which is even slightly higher than that before the cycle, reflecting good cycle stability performance. At the same time, the platform pressure does not change significantly.

[0045] Example 2, a method for preparing an in-situ dual-phase vanadium-based hydrogen storage material, comprising the following steps:

[0046] This embodiment is basically the same as embodiment 1, except that: vanadium particles (1 g) and titanium tetrachloride are mixed and ball-milled in a mass ratio of 50:1, the ball-to-material ratio is 50:1, the ball milling speed is 400 rpm, and after ball milling for 6 hours, an in-situ dual-phase vanadium-based hydrogen storage material is obtained.

[0047] Figure 8 The XRD pattern of the in-situ dual-phase vanadium-based hydrogen storage material is shown in Figure 2. Only V is observed in the product, with no other components observed.

[0048] Figure 9(a), (b) and (c) are the V2p XPS spectra, Ti 2p XPS spectra and Cl 2p XPS spectra of the in-situ dual-phase vanadium-based hydrogen storage material prepared in this example. It can be seen that similar to Example 1, the V in the material is mainly 0-valent V, accompanied by a small amount of V 4+ , Ti then exists at the same time 4+ and Ti 0 , and the XPS signal of Cl can still be observed. This indicates that the material also contains Ti(V)Cl4 phase and VTi solid solution phase. This example also prepared a VTi-based two-phase hydrogen storage alloy doped with Ti(V)Cl4 in situ.

[0049] Figure 10 This is the isothermal hydrogen absorption kinetics curve of the in-situ dual-phase vanadium-based hydrogen storage material at 30° C. when first activated in this embodiment. The maximum hydrogen absorption capacity can reach 3.2 wt %.

[0050] Figure 11 This is a PCT curve of hydrogen release of the in-situ dual-phase vanadium-based hydrogen storage material prepared in this example at 50° C., with a plateau pressure of 8.3 bar and an effective hydrogen storage capacity of 1.52 wt%.

[0051] In a comparative example, crushed vanadium particles were prepared using step 1 of Example 1.

[0052] Figure 12 The isothermal hydrogen absorption kinetics curve of the V particles prepared in this comparative example at 30° C. during initial activation shows that the hydrogen absorption capacity of the pure V particles is only 2.01 wt % even after 30,000 s, indicating poor activation performance.

[0053] Figure 13 (a) is the isothermal hydrogen absorption kinetics curve of the V particles prepared in the comparative example at 30°C, 50°C, 80°C, and 100°C. (b) is the Arrhenius curve plotted based on the isothermal kinetics curves at different temperatures. The calculated hydrogen absorption activation energy is 43.15 kJ·mol -1 , the hydrogen absorption kinetics performance is poor.

[0054] Comparison of the Examples and Comparative Examples of the present invention demonstrates that the in-situ dual-phase vanadium-based hydrogen storage material prepared using the preparation method of the present invention exhibits superior activation performance and hydrogen absorption kinetics without sacrificing maximum and effective hydrogen storage capacity, demonstrating a highly efficient method for modifying the performance of V-based hydrogen storage materials. Example 1 is the preferred embodiment of the present invention.

[0055] The above description is an explanation of the specific implementation of the present invention, rather than a limitation of the present invention. Those skilled in the relevant technical field can also make various equivalent technical solutions without departing from the scope of the present invention, so all equivalent technical solutions should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an in-situ dual-phase vanadium-based hydrogen storage material, characterized in that: After vacuum heat treatment of the vanadium block, hydrogen pressure is added at room temperature for hydrogenation and crushing to obtain vanadium particles; the vanadium particles are mixed with titanium tetrachloride for ball milling reaction; and after another step of heat treatment, a dual-phase vanadium-based hydrogen storage material is prepared.

2. The method for preparing an in-situ dual-phase vanadium-based hydrogen storage material according to claim 1, characterized in that: The vacuum heat treatment temperature is 500-600°C.

3. The method for preparing an in-situ dual-phase vanadium-based hydrogen storage material according to claim 1, characterized in that: The hydrogen pressure of the hydrogenation crushing is 50-100 bar.

4. The method for preparing an in-situ dual-phase vanadium-based hydrogen storage material according to claim 1, characterized in that: The vacuum heat treatment and hydrogenation treatment are performed 3-5 times.

5. The method for preparing an in-situ dual-phase vanadium-based hydrogen storage material according to claim 1, characterized in that: The ball milling reaction is carried out in an inert atmosphere or a vacuum environment at room temperature.

6. The method for preparing an in-situ dual-phase vanadium-based hydrogen storage material according to claim 1, characterized in that: The mass ratio of the vanadium particles to titanium tetrachloride is 20-100:

1.

7. The method for preparing an in-situ dual-phase vanadium-based hydrogen storage material according to claim 1, characterized in that: The ball milling method is planetary ball milling, stainless steel beads are used, the ball-to-material ratio is 30-100:1, the ball milling speed is 300-400 rpm, and the ball milling time is 3-6 hours.

8. The method for preparing an in-situ dual-phase vanadium-based hydrogen storage material according to claim 1, characterized in that: The one-step heat treatment is carried out in a vacuum environment at a temperature of 500-600° C. for 2-3 hours.

9. An in-situ dual-phase vanadium-based hydrogen storage material prepared by the preparation method according to claim 1.

10. Use of the in-situ dual-phase vanadium-based hydrogen storage material according to claim 9 in the field of solid-state hydrogen storage.

Citation Information

Patent Citations

  • A vanadium-titanium-based hydrogen storage alloy powder and its preparation method

    CN114381644B